Crystal structure, morphology and luminescent properties of rare earth ion-doped SrHPO4 nanomaterials - 王梦楠 田博士 岳丹 鲁伟 于明丽 李春阳 李庆锋 王振领 (中国稀土学报：英文版, 2015)
Undoped and rare earth ions （Eu3＋, Ce3＋, Tb3＋） doped β-SrHPO4 nanomaterials were successfully prepared by a facile hydrothermal method. The crystal structure, morphology and luminescent properties were characterized by X-ray powder diffraction （XRD）, scanning electron microscopy （SEM）, transmission electron microscopy （TEM）, photoluminescence （PL） spectra and lumi- nescence decay curves. The results indicated that the tmdoped and rare earth ions doped SrHPO4 nanomaterials （the doping concen- tration was not above 7%） were well crystallized, with the same crystal structure （~-SrHPO4）. Nevertheless, the doping of rare earth ions could lead to the changing of morphology from nanoflakes to nanocrystals. Under the excitation of UV light, rare earth ions （Eu3＋, Ce3＋, Tb3＋） doped I3-SrHPO4 nanocrystals exhibited the characteristic emission of Eu3＋, Ce3＋ and Tb3＋ ions, respectively. The luminescence decay curves of [3-SrHPO4：Eu3＋ and D-SrHPO4：Ce3＋,Th3＋ nanocrystals conformed to the double exponential fluores- cence decay, and the average lifetimes were 1.14 and 4.12 ms, respectively. The luminescence decay curve of 13-SrHPO4：Ce3＋ was fitted into a single exponential function, and the lifetime was about 0.78 ns.